1988
DOI: 10.1147/rd.325.0603
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry at interfaces: Electropositive metals on polymer surfaces

Abstract: This paper presents a study of chemical interactions between polymer surfaces and metal atoms deposited from the vapor phase. Such interactions may play an important role in interfacial metal-polymer adhesion. The chemical nature of the interface formed when an electropositive metal (chromium or cesium) is deposited onto the surface of PMDA-ODA polyimide has been investigated using chemical model studies coupled with photoelectron spectroscopic techniques. X-ray photoelectron spectroscopy, synchrotron-radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…After curve fitting N 1s spectra reveals its presence in two forms (Fig. 4(b)), the major peak at BE of 400.2 eV suggests for NO or NH 23,24) and another peak at BE of 399.3 eV for CrN/Cr 2 N. 25) Considering potential-pH equilibrium diagram for N-H 2 O system 26) it is noticed that NH 4 ϩ ions are stable at lower potential and NO 3 Ϫ ions are at higher potential. Hence, in the present study for the given potential (100 mV SCE ) and pH (0.5), NO is more likely to form.…”
Section: Resultsmentioning
confidence: 97%
“…After curve fitting N 1s spectra reveals its presence in two forms (Fig. 4(b)), the major peak at BE of 400.2 eV suggests for NO or NH 23,24) and another peak at BE of 399.3 eV for CrN/Cr 2 N. 25) Considering potential-pH equilibrium diagram for N-H 2 O system 26) it is noticed that NH 4 ϩ ions are stable at lower potential and NO 3 Ϫ ions are at higher potential. Hence, in the present study for the given potential (100 mV SCE ) and pH (0.5), NO is more likely to form.…”
Section: Resultsmentioning
confidence: 97%
“…Aluminum, having a higher affinity to oxygen than copper, can orient carbonyl groups in polymers such as poly(ethyleneterephthalate) [17,18] or polyamide [24][25][26]. Furthermore, the electrochemical potentials of PA 11 and Al favor the electron transfer from the metal to the polymer.…”
Section: Resultsmentioning
confidence: 99%
“…This, as suggested previously, is considered to be the initial step of polymer-metal interaction [4]. Possibly, aluminum reacts with the carbonyl group, opening the C=O double bond, to form a complex involving a -C-O-A1 sequence [24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult to determine the reactivity of Cr with oxygen by the AES analysis. XPS studies have shown the presence of chemical bonding states between Cr and 0 in the very carefully controlled interfaces formed under UHV conditions [22,23]. An XPS study on the peeled surface may be necessary to resolve the nature of the bonding state of Cr to polyimide in the interface formed under realistic processing conditions.…”
Section: Aes Analysis On the Bulk Polyimide Surfacementioning
confidence: 99%